A study on demographical, clinical-radiological, and histopathological profile of bronchial carcinoma in a tertiary care hospital in Bangladesh - Chakrabortty, Rajashish; Siddiqua, Dibanur Rashid; Rahman, Samia; Paul, Susanta Kumar (International Journal of Research in Medical Sciences, 2023)
Background: Bronchial carcinoma has different demographical, clinico-radiological, and histopathological profiles depending on the environment, gender, and racial group. The purpose of this study was to explore the sociodemographical, clinical, radiological, and histopathological patterns of bronchial carcinoma in Bangladesh. Methods: This cross-sectional descriptive study was conducted at the respiratory medicine department of Bangabandhu Sheikh Mujib Medical University (BSMMU). The study period was one year from January 2021 to December 2021. Our study documented socio-demographic patterns, smoking habits, history of COPD, clinical features, radiological findings, histopathological patterns of the tumor, and participants’ performance status. Results: One hundred histopathologically confirmed patients with bronchial carcinoma were included in this study. The mean age of the participants was 59.57±10.41 years. The majority of the participants were in the 5th and 6th decade, 35% and 34% respectively. Smokers were 80% in our study. The presenting complaints were cough (87%), shortness of breath (61%), and chest pain (58%). Mass lesions (83%) followed by collapse (8%) were the most common imaging findings. Adenocarcinoma (48%) and squamous cell carcinoma (35%) were the predominant histological types. Conclusions: The histopathological profiles of bronchial carcinoma are changing and adenocarcinoma is becoming the predominant type in Bangladesh.